ANALISIS BENTUK KEPEDULIAN ORANG TUA TERHADAP PENDIDIKAN AGAMA ANAK - Zulya Ifla Alvina; Meyniar Albina (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
This study aims to determine the form of parental concern for children in terms of implementing the values of Islamic religious education in Pulau Kampai Village, Kec. Kab. Langkat Kec. Pangkalan Susu. In this qualitative descriptive research, data was collected through observation, interviews, and documentation. The results of the study show that the form of concern that parents do for their children is guiding their children by taking direct action and participating in practice not only ordering, paying attention to children's learning, forbidding good morals to parents and others, motivating by helping and developing ways of learning their children, advising children about their rights and obligations as children who are obliged to serve their parents, as well as providing rewards and punishments to children. Supporting factors in the form of parents' awareness of the importance of religious education for children. The inhibiting factors faced by parents are that there are still people whose economic conditions are lacking, as well as media factors that influence children's mindsets. Data collection methods are carried out in three ways, namely observation, interviews, and documentation. Furthermore, the data analysis techniques that the researchers used were data reduction, data display, and conclusion-drawing verification. Then check the validity of the data is done by extending observations, increasing persistence in research, triangulation, and member checks.